2010
DOI: 10.1016/j.jprot.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Use of proteomics for validation of the isolation process of clotting factor IX from human plasma

Abstract: The use of proteomic techniques in the monitoring of different production steps of plasma-derived clotting factor IX (pd F IX) was demonstrated. The first step, solid-phase extraction with a weak anion-exchange resin, fractionates the bulk of human serum albumin (HSA), immunoglobulin G, and other non-binding proteins from F IX. The proteins that strongly bind to the anion-exchange resin are eluted by higher salt concentrations. In the second step, anion-exchange chromatography, residual HSA, some proteases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Residual impurities that were still present in the F IX fraction, such as IaIp and vitronectin, were removed by nanofiltration, as documented by use of iTRAQ quantitation methods. The final product was pure F IX, with a specific activity greater than 200 IU/ mg protein [3,12]. These two papers [3,12] show that use of proteomic techniques can significantly extend the knowledge of this industrial process.…”
Section: Clotting Factor IXmentioning
confidence: 95%
See 3 more Smart Citations
“…Residual impurities that were still present in the F IX fraction, such as IaIp and vitronectin, were removed by nanofiltration, as documented by use of iTRAQ quantitation methods. The final product was pure F IX, with a specific activity greater than 200 IU/ mg protein [3,12]. These two papers [3,12] show that use of proteomic techniques can significantly extend the knowledge of this industrial process.…”
Section: Clotting Factor IXmentioning
confidence: 95%
“…These two papers [3,12] show that use of proteomic techniques can significantly extend the knowledge of this industrial process. In addition to the identification of impurities, the use of iTRAQ methods in the MS analysis also provides quantitative information about the degree of their removal [12,106].…”
Section: Clotting Factor IXmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of prothrombin complex concentrates (PCCs) was used as a model to evaluate to what extent these technologies can detect differences in blood‐derived therapeutics beyond that of standard quality control tests [16]. Additional studies have reported on fractionated blood products including FVIII and FVIII/von Willebrand factor concentrates [17] and FIX concentrates [18]. These studies showed a surprising degree of difference between products from different manufacturers but revealed low batch to batch variability of single products.…”
Section: Plasma Proteomicsmentioning
confidence: 99%